Replication and expression of Xenopus laevis globin genes injected into fertilized Xenopus eggs. - Bendig, M M (1983)
Cloned Xenopus adult alpha 1- and beta 1-globin genes were injected into fertilized Xenopus eggs, and the eggs were allowed to develop into swimming tadpoles. The injected DNA replicated during early Xenopus development but did not become methylated de novo. When DNA was modified with Hpa II methylase before injection, methylation was maintained during replication. Although the Xenopus adult globin genes are not normally expressed until metamorphosis, both the unmethylated and in vitro methylated adult alpha- and beta-globin genes were transcribed at low levels, but from the correct promoters, during early development.